PERBANDINGAN GAYA BELAJAR TERHADAP KETERAMPILAN PROSES SAINS PESERTA DIDIK - Hernawati, Diana; Hardin, Arimbi Rizki (Jurnal Metaedukasi: Jurnal Ilmiah Pendidikan, 2019)
Each student has their own way of receiving and processing information or it called a learning style. Learning style is an important learning modality for educators to consider in learning, because the fact is that not all students achieve the same learning goals. This study aims to determine the comparison of visual, auditory and kinesthetic learning styles to the science process skills in 10th grade of state high school 1 Sukahaji. This research is a quantitative study with pre-experimental research design in the from of one-group pretest-posttest design. The study population was the entire 10th grade of public high school 1 Sukahaji 2018/2019 school year. Samples were taken by purposive sampling technique. Data obtained through cognitive aspects of science process skills test. Hypothesis testing using the ANOVA test, then further tests using the Tukey test. The results of the study generally showed that there were differences in the science process skills of students who tended towards visual, auditory and kinesthetic learning styles with a pretest significance value of science process skills by 0,04 and a significance value of the posttest of science process skills by 0,02. Based on this it can be concluded that there are differences in the science process skills of students based on their learning styles, in this study kinesthetic learning styles are more dominant than visual learning styles and auditory learning styles